Zofenopril and incidence of cough: a review of published and unpublished data - Omboni S; Borghi C (Dove Medical Press, 2011)
Stefano Omboni1, Claudio Borghi21Italian Institute of Telemedicine, Varese, Italy; 2Department of Internal Medicine, Aging, and Kidney Diseases, University Hospital of Bologna, Bologna, ItalyObjective: Cough is a typical side effect of angiotensin-converting enzyme (ACE) inhibitors, though its frequency quantitatively varies among the different compounds. Data on the incidence of cough with the lipophilic third-generation ACE inhibitor zofenopril are scanty and never systematically analyzed. The purpose of this paper is to give an overview on the epidemiology, pathophysiology, and treatment of ACE inhibitor-induced cough and to assess the incidence of cough induced by zofenopril treatment.Methods: Published and unpublished data from randomized and postmarketing zofenopril trials were merged together and analyzed.Results: Twenty-three studies including 5794 hypertensive patients and three studies including 1455 postmyocardial infarction patients exposed for a median follow-up time of 3 months to zofenopril at doses of 7.5–60 mg once-daily were analyzed. The incidence of zofenopril-induced cough was 2.6% (range 0%–4.2%): 2.4% in the hypertension trials (2.4% in the double-blind randomized studies and 2.4% in the open-label postmarketing studies) and 3.6% in the double-blind randomized postmyocardial infarction trials. Zofenopril-induced cough was generally of a mild to moderate intensity, occurred significantly (P < 0.001) more frequently in the first 3–6 months of treatment (3.0% vs 0.2% 9–12 months), and always resolved or improved upon therapy discontinuation. Zofenopril doses of 30 mg and 60 mg resulted in significantly (P = 0.042) greater rate of cough (2.1% and 2.6%, respectively) than doses of 7.5 mg and 15 mg (0.4% and 0.7%, respectively). In direct comparison trials (enalapril and lisinopril), incidence of cough was not significantly different between zofenopril and other ACE inhibitors (2.4% vs 2.7%).Conclusion: Evidence from a limited number of studies indicates a relatively low incidence of zofenopril-induced cough. Large head-to-head comparison studies versus different ACE inhibitors are needed to highlight possible differences between zofenopril and other ACE inhibitors in the incidence of cough.Keywords: cough, ACE inhibitor, zofenopril, arterial hypertension, myocardial infarction, heart failure